The effect of the laryngeal mask airway on the outcomes of the endoscopic tympanoplasty (Annals of Medical Research, 2021)
Aim: Chronic otitis media is a common disease characterized by a tympanic membrane perforation and conductive hearing loss. Tympanoplasty is performed to provide a healthy middle ear and to create an intact eardrum. In recent years, endoscopic tympanoplasty has become more popular for the repair of the tympanic membrane. This method saves time for the surgeon and provides a comfortable opportunity for the patient.Endotracheal intubation (ET) and laryngeal mask airway (LMA) are two different airway systems used in general anesthesia. It is known that LMA provides shorter operating times for surgeries requiring general anesthesia.The aim of this study was to evaluate the outcomes of endoscopic tympanoplasty in patients who underwent endoscopic tympanoplasty with LMA or ET anesthesia, and to compare this method that regards to graft success rates. We also investigated the duration of surgery and operation time, and pain scores in both groups.Materials and Methods: In this retrospective study, we included the patients who were performed endoscopic type 1 tympanoplasty with tragal cartilage graft. Visual evaluation of eardrums and audiologic datas of the patients were performed. The cases with cholesteatoma and/or ossicular chain problem were not included to study. Patients were evaluated in two different groups as LMA and endotracheal tube (ET) group. Preoperatively perforation types and audiological data; intraoperatively operation and surgical times; postoperatively 3th month surgical success, pain scores and audiological results were recorded in each group. And these results were evaluated statistically to compare the differences between LMA and ET group.Results: Ninety-three patients were included in the study and 36 of them underwent endoscopic tympanoplasty with LMA and 57 patients with ET. The surgery time was similar in both groups (p> 0.05), but the operation time was statistically significantly shorter in the LMA group (p 0.05). Graft success rates and hearing gain were higher in the LMA group but not statistically significant.Conclusions: We observed that endoscopic tympanoplasty with LMA or ET had similar surgery time, graft success rate, and pain scores, but total operation time was significantly shorter in the LMA group. As a result, LMA can be considered as a suitable method for endoscopic tympanoplasty.
Keywords: Chronic otitis media; endoscopic tympanoplasty; laryngeal mask airway